Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Zapisz w postaci sumy algebraicznej 4.67 gwiazdek na podstawie 6 opinii

`a)\ (x-4)^2=x^2-2*x*4+4^2=x^2-8x+16` 

`b)\ (9+x)^2=9^2+2*9*x+x^2=81+18x+x^2` 

`c) \ (x-1/4)^2=x^2-2*x*1/4+(1/4)^2=x^2-1/2x+1/16` 

`d)\ (x+6y)^2=x^2+2*x*6y+(6y)^2=x^2+12xy+36y^2` 

`e)\ (2x-5y)^2=(2x)^2-2*2x*5y+(5y)^2=4x^2-20xy+25y^2` 

`f)\ (6x+1/2y)^2=(6x)^2+2*6x*1/2y+(1/2y)^2=36x^2+6xy+1/4y^2` 

`g)\ (x^2+3)^2=(x^2)^2+2*x^2*3+3^2=x^4+6x^2+9` 

`h)\ (x^2-2y)^2=(x^2)^2-2*x^2*2y+(2y)^2=x^4-4x^2y+4y^2`